Pengelolaan Wakaf - Yenni Samri Juliati; Mahlia Putri HSB (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Waqf is one of the people's economic instruments that can be used to empower the people's economy. In terms of terminology, waqf comes from the word waqfu which means to stop or hold something. The current phenomenon is the management of zakat in cash. Consumer orientation towards waqf tends to encourage leaders to make managers avoid productive efforts. As a result, waqf is used directly and not invested effectively. This research was conducted using a descriptive method with a qualitative approach based on data sources from literature studies and observations. The aim of this research is to provide information related to waqf management. The research results show that the management of cash waqf funds as an investment instrument is attractive, because the benefits from this investment - in the form of investment profits - can be enjoyed by people everywhere, both locally, regionally and internationally. This is possible because the benefits of the investment are in the form of cash which can be transferred to any beneficiary throughout the world.